Practical Aspects of the Use of Carfilzomib in Multiple Myeloma - SV Semochkin; GN Salogub; SS Bessmeltsev; KD Kaplanov (Клиническая онкогематология)
Carfilzomib (Kyprolis®, Amgen), a second-generation proteasome inhibitor, is capable of covalent bonding and irreversible inhibition of the 20S proteasome chymotrypsin-like activity. In 2016 this drug was approved in Russia for monotherapy of relapsed refractory multiple myeloma (MM) and in combination with lenalidomide and dexamethasone (KRd) or only with dexamethasone (Kd) for treatment of patients with relapsed MM after at least one line of prior therapy. The present review outlines mechanism, clinical efficacy, and adverse effects of carfilzomib according to the data of a phase II (monotherapy) trial and two key randomized phase III (carfilzomib combined with other drugs) trials. The ASPIRE trial demonstrated that adding carfilzomib to the combination of lenalidomide and dexamethasone (KRd) significantly improves progression-free survival (PFS) compared with the Rd original regimen (median 26.3 vs. 17.6 months; hazard ratio [HR] 0.69; p = 0.0001). Median overall survival (OS) was 48.3 months (95% confidence interval [95% CI] 42.4–52.8 months) for KRd vs. 40.4 months (95% CI 33.6–44.4 months) for Rd (HR 0.79; p = 0.0045). The ENDEAVOR trial showed that as compared with combination of bortezomib and dexamethasone (Vd) the carfilzomib + dexamethasone (Kd) regimen significantly improves PFS (median 18.7 vs. 9.4 months; HR 0.53; p < 0.0001) and OS (47.6 vs. 40.0 months; HR 0.79; p = 0.010) as well. The present review also discusses how carfilzomib is to be used in special patient groups (with renal failure and high cytogenetic risk).